The Significance of Leadership Style, Organizational Culture and Organizational Citizenship Behavior on Employee Performance: A Quantitative Approach with a Descriptive Method at PT Tunas Digital Indonesia - Chaerunnisa, Indah; Hasan, Diana (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
This research aims to explore the impact of leadership style, organizational culture, and organizational citizenship behavior on employee performance at PT Tunas Digital Indonesia. A quantitative approach with a descriptive method was applied in this study. Data collection was conducted by distributing questionnaires to 56 respondents. The findings reveal that at PT Tunas Digital Indonesia, leadership style has a positive yet insignificant influence on employee performance, while organizational culture significantly and positively affects employee performance. Conversely, organizational citizenship behavior does not exhibit any notable or significant effect on employee performance. The study emphasizes the necessity of establishing a supportive organizational culture, encouraging OCB practices, and enhancing leadership strategies. These insights highlight the critical role of fostering a conducive organizational environment, promoting OCB, and refining leadership approaches to improve employee performance